Etika Berinternet Remaja di Desa 38B Banjarrejo, Kecamatan Batanghari Lampung Timur - A. Lumbu, Aliyandi; Dewi, Puput Sartika (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2022)
The rapid development of information and communication technology has accelerated the acceleration of the globalization process. The form of communication between people has developed along with the development of technology. Communication and interaction are now mostly done using the internet. The purpose of this study was to determine the pattern of internet use in adolescents and to determine the impact of the internet on the ethics of adolescent communication in 38B Banjarrejo village, Batanghari sub-district, East Lampung district. The type of research the author does is field research (Field Research). This research is descriptive qualitative, which is usually referred to as (natural settings). Data collection techniques using interviews, observation, and documentation. The benefits of research are enriching scientific treasures regarding the impact and ways of educating teenagers on the use of the internet in their communication ethics. Based on the results of the study, it was found that: First, the internet has a positive impact on adolescents, the impact is increasing insight in learning, easier communication that is more practical, and increasing general knowledge so that it can be a topic of conversation with their families. Second, the internet also has a negative impact on adolescents. Especially in the ethics of communication. Teenagers spend more time in front of cellphone screens, scrolling social media all day, locking themselves in their rooms. Playing online games to forget their obligations such as helping their parents, reading the Koran, playing with their younger siblings. After getting to know the internet, teenagers become stubborn.